The Movimiento de Izquierda Revolucionaria (MIR) and the armed resistance in Chile during the institutionalization of the dictatorship (1978-1990) - Goicovic, Igor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Movimiento de Izquierda Revolucionaria (MIR) was a political-military organization of Marxist ideology which between 1978 and 1990 defined and deployed in Chile a strategy of armed struggle to confront the dictatorship led by Augusto Pinochet Ugarte. Its objective was to prevent the dictatorship from completing its project of re-founding Chilean society (economically, politically, socially and culturally) and, in this way, to advance towards the development of a socialist revolution.
Keywords: MIR; dictatorship; armed struggle; Chile